ToGatherUp: um protótipo de ferramenta para a construção de corpora - Oliveira, Fernando Paulino de (2019)
This research verifies the effects of incorporating the ToGatherUp tool on both time and effort for building manually the corpus presented herein: the Corpus of Computing in English (CoCLI). We have developed a set of effort measurement metrics – Activity Effort (EA), Total Effort for Text Collection (ETCT) and Total Project Effort (ETP) – which served as the basis for conducting a comparative statistical experiment between the manual elaboration of two identical versions of the CoCLI: which differ from each other by one of them using the ToGatherUp and the other one not using it. The theory and methodology of Corpus Linguistics, together with the concepts from Project Management, subsidized our proposal of systematizing the manual construction of corpora and for creating the two versions of the CoCLI and, along with the notions of the Computing area, guided us in the development of ToGatherUp. The experiment shows an average reduction of 7.47% in the ETP when using ToGatherUp compared to the ETP when not using the tool. This result corroborates the hypothesis that the tool reduces the time and effort spent by the researcher on manual elaboration projects of corpora.